2022
DOI: 10.1007/jhep05(2022)128
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Hawking-Page phase transition with the non-Markovian effects

Abstract: Based on the free energy landscape description of Hawking-Page phase transition, the transition process from the Schwarzschild-anti-de Sitter black hole to the thermal anti-de Sitter space are considered to be stochastic under the thermal fluctuations. If the correlation time of the effective thermal bath is comparable or even longer than the oscillating time of the spacetime state in the potential well on the free energy landscape, the non-Markovian model of the black hole phase transition is required to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…For the intermediate friction ζ = 3.5, the competition of the two behaviors leads to the non-monotonic behavior of the transition rate with respect to the decay coefficient γ as shown in Figure 8. Note that the speed up behavior of the transition process in the large friction regime has been observed previously [33]. The reason behind is that the non-Markovian effect introduces more time scales and therefore equivalently more degrees of freedom.…”
Section: Dynamics Of Hawking-page Phase Transitionsupporting
confidence: 59%
See 2 more Smart Citations
“…For the intermediate friction ζ = 3.5, the competition of the two behaviors leads to the non-monotonic behavior of the transition rate with respect to the decay coefficient γ as shown in Figure 8. Note that the speed up behavior of the transition process in the large friction regime has been observed previously [33]. The reason behind is that the non-Markovian effect introduces more time scales and therefore equivalently more degrees of freedom.…”
Section: Dynamics Of Hawking-page Phase Transitionsupporting
confidence: 59%
“…The generalized Langevin equation is an integro-differential equation where the integral term reflects the memory effect or the non-Markovian effect of the effective thermal bath from the underlying degrees of freedom of the black hole. It should be noted that the framework of the non-Markovian model of black hole phase transition has been briefly introduced in [33], where the transition rate of the non-Markovian dynamics of black hole phase transition was derived and used to study the kinetics of the Hawking-Page phase transition. It was shown that the non-Markovian effect or the memory effect can promote the dynamical process of Hawking-Page phase transition.…”
mentioning
confidence: 99%
See 1 more Smart Citation